2001
DOI: 10.1182/blood.v98.6.1897
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in drug-induced DNA double-strand breaks associated with β1 integrin–mediated adhesion correlates with drug resistance in U937 cells

Abstract: We previously showed that adhesion of myeloma cells to fibronectin (FN) by means of ␤1 integrins causes resistance to certain cytotoxic drugs. The study described here found that adhesion of U937 human histiocytic lymphoma cells to FN provides a survival advantage with respect to damage induced by the topoisomerase (topo) II inhibitors mitoxantrone, doxorubicin, and etoposide. Apoptosis induced by a topo II inhibitor is thought to be initiated by DNA damage. The neutral comet assay was used to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 29 publications
0
79
0
1
Order By: Relevance
“…30 Furthermore, integrin-mediated adhesion in hemapoeitic cancer cells reduced DNA double-strand breaks and apoptosis caused by chemotherapeutic agents such as mitoxantrone and etoposide. 31 This primarily a5b1-mediated reduction in DNA damage correlated with decreased topoisomerase-II enzymatic activity. However, the a5b1 integrin is not found in SCLC cells and is reduced in other carcinomas.…”
Section: Discussionmentioning
confidence: 95%
“…30 Furthermore, integrin-mediated adhesion in hemapoeitic cancer cells reduced DNA double-strand breaks and apoptosis caused by chemotherapeutic agents such as mitoxantrone and etoposide. 31 This primarily a5b1-mediated reduction in DNA damage correlated with decreased topoisomerase-II enzymatic activity. However, the a5b1 integrin is not found in SCLC cells and is reduced in other carcinomas.…”
Section: Discussionmentioning
confidence: 95%
“…The examination of various transformed cell lines and primary cell strains has raised evidence for chemo-and radioprotective effects of specific ECM proteins (Vlodavsky et al, 1980;Fuks et al, 1992;Rose et al, 1999;Hazlehurst et al, 2001;Cordes et al, 2002Cordes et al, in press (a), 2003Cordes and Meineke, 2003;. As reported (Bouterfa et al, 1999;Oz et al, 2000;Mahesparan et al, 2003), FN, laminin, collagen-IV and -I, decorin, tenascin and vitronectin are ECM proteins produced and secreted by cells of malignant tumours of glial origin in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Each heterodimer consists of one a-and one b-chain. Integrins are involved in the regulation of several cell functions such as differentiation, cell cycle progression, apoptotic pathways and DNA repair mechanisms (Adams and Watt, 1990;Assoian, 1997;Hazlehurst et al, 2001). To date avb3 (Brooks et al, 1996;Rooprai et al, 1999), a5b1 (Ohnishi et al, 1998) and other b1-integrin combinations (Paulus et al, 1993;Chintala et al, 1996;Friedlander et al, 1996) have been identified to participate in cell migration and invasion.…”
mentioning
confidence: 99%
“…18,19,24,[32][33][34] MM is a latent disease of the BM, where the tumor cell phenotype likely reflects a combination of multiple interactions including cell-cell, cell-ECM, and cellgrowth factor. In this study, we demonstrate that the presence of BMSCs during treatment of H929 or RPMI 8226 cells with mitoxantrone significantly reduces apoptosis in myeloma cell lines.…”
Section: Discussionmentioning
confidence: 99%